Combined control of combustion load and combustion position in a moving grate biomass furnace - Paces, Nicole; Voigt, Andreas; Jakubek, Stefan; Schirrer, Alexander; Kozek, Martin (2011 19th Mediterranean Conference on Control and Automation, 2011)
This work presents a combined combustion load and combustion position control for a moving grate biomass furnace. The control design is based on a linearized reduced order model of the process and comprises model predictive control (MPC) with an additional proportional-integral (PI) feedback loop. An analysis for closed-loop stability as well as simulation results are presented. The results demonstrate the effectiveness of the proposed concept.